1982
DOI: 10.1093/oxfordjournals.bmb.a071769
|View full text |Cite
|
Sign up to set email alerts
|

The Physiology of Cholecystokinin in Brain and Gut

Abstract: PHYSIOLOGY OF CHOLECYSTOKININ IN BRAIN AND GUT GJDockray used in biological studies before it became clear that this fragment existed naturally in its own right The identification of CCK8 was made first in extracts of brain of the rat, pig, dog and man, and followed reports of gastrin-like immunoreactivity in brain (Vanderhaeghen et al. 1975; Dockray, 1976; Muller et al. 1977; Rehfeld, 1978). The latter material was reported to occur in high concentrations in cerebral cortex and to have the gel-filtration prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…In this context, it is worth noting that the CCK receptors in the gall bladder and the pancreatic acini seem to be located on nonneuronal cells (Yau et al, 1973;Williams, 1982), whereas those in the guinea-pig ileum are located on enteric neurones (see Introduction). It would appear, therefore, that peripheral CCK receptors share a similar sensitivity to CR 1409 which is independent of their location, an assumption that has also been raised by Dockray (1982) with regard to dibutyryl cyclic guanosine monophosphate. The specificity of CR 1409 as a CCK antagonist was proved by the finding that contractions of the longitudinal and circular muscles of the guinea-pig ileum, induced by a variety of non-CCK agonists, were not affected.…”
Section: Discussionmentioning
confidence: 89%
“…In this context, it is worth noting that the CCK receptors in the gall bladder and the pancreatic acini seem to be located on nonneuronal cells (Yau et al, 1973;Williams, 1982), whereas those in the guinea-pig ileum are located on enteric neurones (see Introduction). It would appear, therefore, that peripheral CCK receptors share a similar sensitivity to CR 1409 which is independent of their location, an assumption that has also been raised by Dockray (1982) with regard to dibutyryl cyclic guanosine monophosphate. The specificity of CR 1409 as a CCK antagonist was proved by the finding that contractions of the longitudinal and circular muscles of the guinea-pig ileum, induced by a variety of non-CCK agonists, were not affected.…”
Section: Discussionmentioning
confidence: 89%
“…sium excretion; an overall effect resembling the potassium-sparing diuretics, amiloride and triamterene (Reineck & Stein, 1981). The rise in plasma glucose concentration observed during CCK8 infusion in the rabbit may, or may not, be direct (Unger et al, 1967;Dockray, 1981), but could be a factor in CCK8-induced appetite suppression (Dockray, 1982).…”
Section: Main Effects In Rabbit and Manmentioning
confidence: 99%
“…One such response is the mediation of nutrient-induced inhibition of gastric emptying (49). Similar to 5-HT, one mechanism by which CCK suppresses food intake is through its ability to inhibit gastric emptying (3,12,19,36,40,43,55).Previous studies have shown an interaction between the serotonergic and cholecystokinergic systems in the control of food intake (7,8,47). Although original exploration of this interaction focused on central serotonergic activity, recent reports (11), including those from our own laboratory (22), have shown that systemic administration of a selective 5-HT 3 receptor antagonist attenuates CCK-induced satiation.…”
mentioning
confidence: 99%
“…One such response is the mediation of nutrient-induced inhibition of gastric emptying (49). Similar to 5-HT, one mechanism by which CCK suppresses food intake is through its ability to inhibit gastric emptying (3,12,19,36,40,43,55).…”
mentioning
confidence: 99%